Urinary Ultrasound and Other Imaging for Ureteropelvic Junction Type Hydronephrosis (UPJHN) - Ucar, Ayse Kalyoncu; Kurugoglu, Sebuh (Frontiers in Pediatrics, 2020)
Abstract Ultrasound is the main imaging study used to diagnose ureteropelvic junction (UPJ) obstruction. On ultrasound, abnormal dilatation of the pelvicalyceal system of varying degrees is seen, whereas the ureter is normal in caliber. A properly performed study provides essential information regarding laterality, renal size, thickness, and architecture of the renal cortex and degree of dilatation of the pelvicalyceal system. Doppler ultrasound may identify a crossing vessel, when present. This imaging method also has been used differentiating obstructive from nonobstructive hydronephrosis by renal arterial resistive index measurements. Abdominal radiographs may show soft tissue fullness, bulging of the flank, and displacement of bowel loops from the affected side. The voiding/micturating cystourethrogram helps exclude other causes of upper tract dilatation, including vesicoureteral reflux, urethral valves and ureteroceles. Computerized Tomography angiography with multiplanar reformatted and three-dimensional images may be used to depict suspected crossing vessels as a cause of UPJ obstruction in older children and adults. Magnetic Resonance Urography has progressed significantly in recent years due to the development of both hardware and software that are used to generate high-resolution images. This imaging technique currently allows for the detailed assessment of urinary tract anatomy, while also providing information regarding renal function, including differential renal function, and the presence or absence of obstructive uropathy.